The eyes reveal uncertainty about object distinctions in semantic variant primary progressive aphasia. (June 2018) - Faria, Andreia V.; Race, David; Kim, Kevin; Hillis, Argye E.
Abstract: At least three distinct variants of primary progressive aphasia (PPA) have been described, but they are difficult to distinguish early in the course, when individuals experience primarily anomia. People with svPPA are often the hardest to care for, because they have impaired comprehension of words and objects and often have negative changes in comportment. We sought to identify an early marker of semantic variant primary progressive aphasia (svPPA) and to enhance the understanding of the semantic deficit in svPPA. We hypothesized that the pattern of eye tracking in a word picture matching task can differentiate svPPA from other variants and can predict which participants with unclassifiable PPA will progress to svPPA. We tested 19 individuals with PPA on a word picture matching task with eye tracking. We found that individuals with svPPA were less accurate than other variants when the foils were semantic coordinates (horse-cow) or schematically related (horse-saddle), but not when they were thematically related (saw-horse) or unrelated. Moreover, even in the condition in which they were highly accurate (unrelated foils) they looked much more often to the foils and for longer, than other variants or controls. Unclassifiable PPA participants who eventually developed svPPA showed the same pattern. This abnormal pattern was associated with atrophy in bilateral temporal poles.